2021
DOI: 10.7717/peerj.11799
|View full text |Cite
|
Sign up to set email alerts
|

Ambulacrarian insulin-related peptides and their putative receptors suggest how insulin and similar peptides may have evolved from insulin-like growth factor

Abstract: Background Some insulin/IGF-related peptides (irps) stimulate a receptor tyrosine kinase (RTK) that transfers the extracellular hormonal signal into an intracellular response. Other irps, such as relaxin, do not use an RTK, but a G-protein coupled receptor (GPCR). This is unusual since evolutionarily related hormones typically either use the same or paralogous receptors. In arthropods three different irps, i.e. arthropod IGF, gonadulin and Drosophila insulin-like peptide 7 (dilp7), likely evolve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…(c) Conserved functional features. As one of the most important hormone growth factors, the growth-regulatory role of the insulin superfamily has been demonstrated in a variety of animals ( 8 , 22 , 54 ). In this study, the apparent growth-inhibitory phenotypes by both CRISPR/Cas9 and RNAi approaches suggested that EcILP was involved in the growth of E. carinicauda .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(c) Conserved functional features. As one of the most important hormone growth factors, the growth-regulatory role of the insulin superfamily has been demonstrated in a variety of animals ( 8 , 22 , 54 ). In this study, the apparent growth-inhibitory phenotypes by both CRISPR/Cas9 and RNAi approaches suggested that EcILP was involved in the growth of E. carinicauda .…”
Section: Discussionmentioning
confidence: 99%
“…and ILP7 in T. castaneum ( 10 ). The emergence of the ILP7 is thought to be traced to a more ancient common ancestor of deuterostomes and protostomes ( 8 , 10 , 15 ). This ancient evolutionary position implies that DILP7/relaxin-like ILP may have more important and broader functions ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to binding to the receptor tyrosine kinase InR, Dilps can also interact with G protein-coupled receptors. For example, Dilp7 and Dilp8 activate the relaxin receptor-like LGR4 and LGR3, respectively (Colombani et al, 2015 ; Gontijo and Garelli, 2018 ; Mita, 2019 ; Veenstra et al, 2021 ; Veenstra, 2021 ). Moreover, Dilp3 functions in intermediate-term memory of aversive olfactory conditioning (Tanabe et al, 2017 ).…”
Section: Iis and Memory In Drosophila Melanogastermentioning
confidence: 99%
“…Two of these genes are likely the ascendants of IGF for one and vertebrate relaxin, arthropod gonadulin and ambulacrarian octinsulin for the second, while the third gave rise to the Drosophila insulin-like peptide 7 (dilp7) orthologs, that are found in insects and other protostomes as well as ambulacrarians. The ambulacrarian data suggests that other, smaller hormones, like insulin, the insect neuroendocrine insulin-like peptides, and the ambulacrarian gonad stimulating substances may have evolved independently from somatomedin and hence are not direct orthologs of one another, but rather the products of convergent evolution (Veenstra, 2020(Veenstra, , 2021a. The term insulin-like peptide and its acronym ilp does not differentiate between these smaller peptides and the triplet consisting of IGF, gonadulin and the dilp7 orthologs.…”
Section: Introductionmentioning
confidence: 99%